DUAL BATTERY CONTROLLER FOR SOLAR BASED ELECTRIC VEHICLE - V., Mohan; Ashokkumar, M.; M., Duraimurugan; R., Sathishkumar; R., Santhosh; K., Jhagannath (International Journal of Research -GRANTHAALAYAH, 2023)
This paper presents the design and implementation of a dual battery controller for a solar-based electric vehicle. The proposed controller manages two batteries: a primary battery that powers the vehicle's electric motor, and a secondary battery that is charged by a solar panel. The controller ensures that both batteries are charged optimally and prevents overcharging or deep discharge. The controller also allows the vehicle to operate solely on the secondary battery when the primary battery is empty, extending the vehicle's range. The design is implemented on an Arduino board and tested in a prototype vehicle. Experimental results show that the dual battery controller increases the vehicle's range and efficiency by effectively utilizing solar power. The proposed controller can be a cost-effective solution for increasing the range of electric vehicles.